Effect of Postural Ergonomics and Static Gluteus Exercise Along with Bridging on Quality of Life in Individual with Mechanical Low Back Pain - Aishwarya Vedpathak1 , Poonam H. Patil2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: This study is to improve the posture of the patient to reduce the excessive stress on the joint and muscular structure It can reduce the mechanical low back pain in the patient .To enhance the performance and productivity of the job and prevent muscle fatigue .It can improve the posture and controls the health of the patient. So we need to study effect of static gluteus exercise along with bridging in patient with mechanical low back pain. Objectives: To find out the effect of static gluteus exercise along with bridging in patient with mechanical low back pain. To find out the effect postural ergonomic who have low back pain. Methodology: The study was carried out in karad area. The subjects were selected according to inclusion and exclusion criteria. Total 26 subjects were participated in this study. Prior consent and assent form was taken. Aim and procedure were explained to the subjects in their preferred language before data collection. The subjects were given static gluteal exercise along with pelvic bridging and postural ergonomic advise also given. Pre and post assessment was done before treatment and after 6 weeks of treatment respectively with the help of Visual analogue scale and the data was analysed with help of appropriate stastical analysis. Result: In conducted study, Visual analogue scale showed statistically significant difference between pre and post treatment values. Pain decreases in individuals. Conclusion: On the basis of the result of the study, it can be concluded that postural ergonomics and static glutes exercise along with pelvic bridging helps in reducing mechanical low back pain and improving quality of life.